Abnormally invasive placenta: an overview of diagnosis and management options - Rajora, Parveen; Singh, Amanjot (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormally invasive placenta, also known as morbidly adherent placenta, is a broad term that describes abnormal adherence of placenta to the underlying myometrium. Clinical risk factors include placenta previa and prior uterine surgery, including caesarean delivery. The diagnosis and management of women at risk is not only based on clinical parameters, but also driven by imaging, namely ultrasound and more recently magnetic resonance (MRI) imaging. Methods: This is a retrospective analysis of 10 cases of abnormally invasive placenta undertaken at Guru Gobind Singh Medical College and Hospital, Faridkot. Results: Hysterectomy done in six cases and uterus was preserved in four cases. Foetal outcome was on average side. Four foetal losses noted two because of prematurity and two due to excessive blood loss admitted with intra uterine foetal death. Two babies needed NICU care but successfully discharged. Conclusions: Newer approaches should be considered investigational until larger prospective series to become available, until then hysterectomy should remain the stay of treatment specially when the family is complete and there is life threatening Haemorrhage.